Non-Islamic elements in the system of religious beliefs of the Belarusian tatar-muslim - Korshunova, Yanina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The article discusses non-Islamic elements in the system of religious beliefs of the ethnocultural group of Belarusian muslim tatars. The features of the emergence and formation of this ethnocultural community in the Belarusian territories are shown, its constitutive features are characterized. The factors that influence the formation of the system of religious beliefs of Belarusian muslim tatars are revealed, its main components are revealed, which are represented by different concrete historical traditions of both monotheistic and non-monotheistic types. The semantic content and reasons for the stability of non-Islamic elements in the religious beliefs of Belarusian muslim tatars are analysed. The meaning and features of the functioning of pre- and non-Islamic elements are shown on the example of some fragments of texts of a healer character, which are found in the corpus of slavic arabic manuscripts.